Disiplin Kerja PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI BANTEN: Displin Kerja - Asep Rahmatullah; Ranthy Pancasasti (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2022)
This study aims to examine the effect of motivation and work discipline on employee performance through job satisfaction as an intervening variable. The study was conducted on ASN employees in the Secretariat of the Regional Legislative Assembly of Banten, amounting to 40 people with census sampling techniques. Analysis of the research data using the SEM-PLS method with the SmartPLS 2.3.m3 application. The results of hypothesis testing show there is no direct influence of work motivation on employee performance. There is a direct influence from work discipline on employee performance. There is a direct effect of work motivation on employee job satisfaction. There is a direct influence from work discipline on employee job satisfaction. There is a direct influence of job satisfaction on employee performance. The mediation test results show job satisfaction can mediate the indirect influence of motivation on employee performance and work discipline on employee performance.